Pengaruh Mingyu Seventeen Sebagai Brand Ambassador Innisfree Terhadap Keputusan Pembelian (Analisis Regresi Linier Pada Followers Akun Twitter @Starfess) - Ayyattika, Hanifah; Tayo, Yanti; Kusumaningrum, Rastri (Jurnal Ilmiah Wahana Pendidikan, 2024)
The Korean Wave phenomenon has significantly affected Indonesian society, affecting various aspects of life, including music, film, drama, and fashion, leading to increased interest in Korean products and commercial communication tactics. K-Pop Indonesia uses new marketing strategies, leveraging Brand Ambassador K-pop to capture public interest, stimulate customer engagement, and influence consumer decision-making. Nowadays in Indonesia, many have already used the Brand Ambassador K-pop for their marketing strategy; one of them is Innsifree, which uses the Korean idol Mingyu Seventeen to capture public interest, stimulate customer engagement, and influence consumer decision-making. The study uses quantitative methodology, collecting data through a Twitter questionnaire from @starfess, a sample consisting of 114 participants. The findings about the influence of Brand Ambassadors on purchasing decisions were found to have a significance of 0.001 < 0.05. Therefore, Ho was rejected and H₁ was accepted.